Avaliação sensorial de cultivares de café arábica em diferentes processamentos na mesorregião do campo das vertentes de Minas Gerais - Ribeiro, Bruno Batista (2018)
The objective of this study was to evaluate the sensory characteristics of coffees from Coffea arabica L. cultivar groups implanted in municipalities located in the mesoregion of Campo das Vertentes, in the state of Minas Gerais, Brazil. After drying, the natural and pulped coffees consisted of 100% mature fruits. We experimented 14 coffee farms located in the municipalities of Carmo da Mata, Oliveira, Santo Antônio do Amparo, and Bom Sucesso, during the harvest of 2016/17. We sampled the fruit from nine groups of commercial coffee cultivars, which were submitted to two types of post-harvest processing, both dry and wet processing, totalizing 250 samples. The sensorial analysis was performed according to the protocol of the Specialty Coffee Association - SCA, consisting of two tasters accredited by the Coffee Quality Institute - CQI. The natural post-harvest processing indicated higher grades for most of the cultivar groups when compared to the pulped processing. Cultivars Topázio, Yellow Bourbon, Yellow Catucaí, Icatu Amarelo, and Icatu Vermelho were prominent for presenting the highest averages for all sensorial attributes.